Empowering community-based water and sanitation services through solar photovoltaic systems: A pathway to energy self-sufficiency - Nurhening Yuniarti; Andik Asmara; Alex Sandria Jawa Wardhana; Eko Swi Damarwan; Maris Setyo Nugroho (University of Merdeka Malang, 2025)
Banyu Bening, an independent community group providing clean water and sanitation services, faces challenges related to energy consumption and water distribution management. The primary issue addressed was the high electricity cost for operating water pumps during the early stages of the business. This problem was particularly critical as the group was newly established and required appropriate technology to overcome these obstacles. Therefore, the main objective of this Community Service Program was to address Banyu Bening’s problems—specifically, the high electricity consumption and low water pressure in the distribution network. The problem-solving process involved several steps: situation analysis, focus group discussions (FGD), material identification, assembly and testing, installation, community socialization, and evaluation. The implemented solution was the installation of a 2kWp solar power system. The final assessment revealed that the system operates optimally, successfully reducing electricity costs by 70 percent.